Potential prognostic and immunotherapeutic value of calponin 1: A pan-cancer analysis - Zhou, Hengli; Ke, Junyu; Liu, Changhua; Zhu, Menglu; Xiao, Bijuan; Wang, Qi; Hou, Rui; Zheng, Yueer; Wu, Yongqiang; Zhou, Xingting; Chen, Xinlin; Pan, Huafeng (Frontiers in Pharmacology, 2023)
Background: Emerging evidence have been prone to suggest a pro-oncogenic role of Calponin 1 (CNN1) in the initiation of a variety of cancers. Despite this, CNN1 remains unknown in terms of its effects and mechanisms on angiogenesis, prognosis, and immunology in cancer. Materials and Methods: The expression of CNN1 was extracted and analyzed via the TIMER, UALCAN, and GEPIA database. Meanwhile, we analyzed the diagnostic value of CNN1 by using PrognoScan and Kaplan-Meier plots. To elucidate the relationships between CNN1 expression and tumor immune-infiltrated cells (TILs), we conducted a correlation study using the TIMER2.0 database. Based on the TISIDB database, immune subtypes or molecular subtypes of CNN1 in cancer were analyzed. The Sangerbox database was used to explore the immune checkpoints. Gene set enrichment analysis (GSEA) was used to analyze the expression pattern and bio-progression of CNN1 in cancer. The expression of CNN1 in gastric cancer was confirmed using immunohistochemistry. To investigate the association between pathological characteristics, clinical prognosis, and CNN1 expression in patients with gastric cancer, we used Cox regression analysis, a semi-parametric regression model. Results: CNN1 expression was higher in normal tissue than tumor tissues of most types of cancers. But the expression level rebounds in the development of tumors. High levels of CNN1 indicated a poor prognosis for 11 tumors, including stomach adenocarcinoma (STAD). There is a relationship between CNN1 and TILs, and marker genes NRP1 and TNFRSF14 of TILs are significantly related to CNN1 expression in gastric cancers. The GSEA results confirmed the lower expression of CNN1 in tumors compared to normal tissues. However, CNN1 again showed an increasing trend during tumor development. In addition, the results also suggest that CNN1 is involved in angiogenesis. The immunohistochemistry results validated the GSEA result (take gastric cancer as an example). Cox analysis suggested that high CNN1 expression was closely associated with poor clinical prognosis. Conclusions: CNN1 was aberrantly elevated in cancers, which would at least positively correlate with angiogenesis and immune checkpoint to contribute to the progression and poor prognosis in various cancers. In the present study, out results thus provided a promising candidate for pan-cancer immunotherapy.